STUDI TENTANG ORGANISASI PKBM (PUSAT KEGIATAN BELAJAR MASYARAKAT) DI KOTA DUMAI - Finola, Ozi; Irja, Desti; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the state of the study of organization seen of the aspects of important from the organisation. Because important aspects of the organization is characteristic the base that must be is used to the development of the study of organization PKBM (Pusat Kegiatan Belajar Masyarakat) In The City Dumai. Formulation problems research is whether the study of organization In The City Dumai in good?. The purpose of this research is to find the study of organization PKBM (Pusat Kegiatan Belajar Masyarakat) In The City Dumai in good. Population in this study some 63 people. Then the researcher determine samples from 39 people to research and 20 people for testing somewhere else, with using a technique simple random sampling. An instrument data collection that is chief to 60 a statement and if the trial live 52 a statement valid for in made instrument research .Data analysis through descriptive analysis quantitative .The outcome of research on three indicators a conclusion can be drawn that study on organizations PKBM (Pusat Kegiatan Belajar Masyarakat) In The City Dumai in good, With the average (the ss+s) 84 %. It means management PKBM run the study of organization, that activities in PKBM run smoothly. Seen from 3 indicators can be concluded that the division and a working relationship were very good, because management PKBM maintain the between her fellow employees , that the activities carried out by going well.Key Words: Study, the study of organization PKBM (Pusat Kegiatan Belajar Masyarakat)